A systematic review and analysis of long-term growth trials on the effect of diet on omega-3 fatty acid levels in the fillet tissue of post-smolt Atlantic salmon - Tom Mock; David Francis; Daniel Drumm; Vincent Versace; BD Glencross; RP Smullen; MK Jago; GM Turchini (2020)
Elucidating the specific effects of diet on the fatty acid composition in Atlantic salmon (Salmo salar), particularly health beneficial omega-3 long-chain polyunsaturated fatty acids (n-3 LC PUFA), remains an area of intense commercial interest given the increasing market restrictions placed on the supply of fishmeal and fish oil. The present study conducted a systematic review and subsequent analysis of published nutritional data from long-term growth trials using post-smolt Atlantic salmon to provide a summary of currently available information and to identify the most significant drivers of omega-3 levels in Atlantic salmon fillet tissue. Overall, there were relatively few studies which met the selection criteria and this had implications for further explanation of some results. Statistically significant regression models were generated for fillet DHA and fillet n-3 LC PUFA. Fish weight was a significant predictor in both models, and dietary 22:6n-3 (DHA) was an intuitive predictor of fillet DHA. Furthermore, dietary EPA and dietary 22:1 isomers were significant predictors of fillet n-3 LC PUFA.